Kebijakan Sinergitas R & D Pemerintah, Komunitas Epistemik, dan Sektor Swasta dalam Percepatan Kemandirian Industri Pertahanan - Endro Tri Susdarwono (Universitas Pancasakti, 2020)
The purpose of this research is to discuss R&D synergy policies of government, epistemic community, and private sector in accelerating the independence of the Indonesian defense industry. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. The government is aware of the importance of building national research capacity in defense technology. That awareness must be followed up with concrete policies, measurable results, and strategic cooperation with other national components. Human resources or researchers, academics, and innovators who are members of various research institutions are basically a